0.73ZrTi2O6–0.27MgNb2O6 microwave dielectric ceramics modified by Al2O3 addition. Issue 11 (23rd May 2018) - He, Lei; Yu, Hongtao; Zeng, Mengshi; Luo, Ting; Liu, Jingsong
Abstract: 0.73ZrTi2 O6 –0.27MgNb2 O6 ceramics with various Al2 O3 contents (0‐2.0 wt%) were prepared by conventional ceramic route. The effects of Al2 O3 on the phase composition, microstructure, conductivity, and microwave dielectric properties were systematically investigated. The coexistence of a disordered α–PbO2 ‐type phase and a rutile second phase was found in all compact ceramics with low Al2 O3 contents ( x = 0, 0.5, and 1.0 wt%), while a corundum phase was detected when Al2 O3 additive increased to 1.5 and 2.0 wt% based on X‐ray diffraction results. With the addition of Al2 O3, the decreased grain size of the matrix phase was observed using field‐emission scanning electron microscope, accompanied with increased resistivity and band‐gap energy. Additionally, Al2 O3 additives efficiently improved the quality factor of the ceramics. After sintering at 1360°C for 3 hours, the ceramic with 1.0 wt% Al2 O3 exhibited excellent microwave dielectric properties: a dielectric constant of 43.8, a quality factor of 33 900 GHz (at 6.6 GHz), and a near‐zero temperature coefficient of resonant frequency (3.1 ppm/ ° C).